Critical literacy in the classroom : the art of the possible - Morgan, Wendy, 1944- (Routledge, 1997)
Critical literacy investigates how forms of knowledge, and the power they bring, are created in language and taken up by those who use texts. It asks how language might be put to different, more equitable uses, and how texts might be recreated in a way that would tell a different story. This book is a carefully documented and critically analysed example of the growing emphasis on critical literacy in syllabuses, government reports and the like. It: bridges the gap between academics' theorizing and teachers' work; describes how secondary teachers have planned and implemented critical literacy curricula on a range of topics, from Shakespeare to the workplace ; listens to teachers reflecting on their teaching and analyses classroom talk ; extrapolates from present practice to a future critical literacy in a digitised, hypermedia world. Teachers and students of education, critical literacy advocates and theorists of literacy and schooling can learn much more from this book, which shows how critical literacy teachers, and their students are contributing to the ongoing reinvention of English education as critical literacy.